PENERAPAN METODE DISTRIBUTION REQUIREMENT PLANNING UNTUK MEMINIMASI BIAYA DISTRIBUSI PT SEKELUARGA - Eko Febrianto; Zeny Fatimah Hunusalela; Aliffia Teja Prasasty (JURNAL REKAYASA SISTEM INDUSTRI, 2020)
Along with increasingly intense competition in any industry or business sector. Demand companies to use methods in order to win the competition. One of them is by doing fast distribution. PT Sekeluarga is one of the companies that distribution of LPG. PT Sekeluarga still has problems such as the inability to distribute goods according to demand, causing a break in the distribution chain and causing scarcity of LPG that occurs at the lowest distribution level or the community. The study was conducted using the Distribution Requirement Planning (DRP) method in addition to that there are also Lot size calculations with Fixed Order Quantity (FOQ), safety stock calculations, and forecasting. The Total Cost (TC) using the company method is Rp. 14,563,117.00. while the Total Cost (TC) using the Distribution Requirement Planning (DRP) method is Rp. 11,676,354.17. From the results of the Total Cost comparison it is found that the Total Cost with the Distribution Requirement Planning method is cheaper when compared to the company method. And by using the Distribution Requirement Planning method also obtained an efficiency of 19.82%.